An Exploration of the Impact of Fitness Apps on Individual Exercise Behaviour - Changdi Luo, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In the contemporary digital landscape, the proliferation of mobile applications (apps) dedicated to sports and fitness has attained unprecedented levels. This research endeavours to explore the nuanced interconnection between the adoption of fitness apps and user engagement in physical exercise, elucidating the underlying dynamics through the lens of exercise behaviour ecology. Employing a comprehensive questionnaire survey, encompassing 868 participants in China, the study delineates its investigative framework. Utilizing the SPSS PROCESS plugin, a moderated mediation model was scrutinized to analyse the data. The outcomes of this inquiry divulge a discernible positive correlation between the utilization of sports and fitness apps and users' engagement in exercise activities. This constructive influence is further expounded through the mediating function of exercise self-efficacy in the association between app usage and exercise behaviour. Additionally, the research underscores the pivotal moderating role of social support in shaping the relationship between exercise self-efficacy and exercise behaviour within the cohort of sports and fitness app users. Essentially, augmented perceived social support enhances the beneficial impact of exercise self-efficacy on exercise conduct. These research findings not only substantiate the affirmative link between sports and fitness apps and exercise behaviour but also furnish valuable insights into harnessing novel media technologies for the advancement of nationwide fitness and health promotion initiatives. The broad scope of the survey, encompassing diverse demographic profiles, underscores the widespread relevance and import of these findings within the domain of sports and fitness app development and utilization.